Automation system in Oyster mushroom cultivation using Mamdani fuzzy logic - Zola, Andrian; Lindawati, Lindawati; Sholihin, Sholihin (Faculty of Engineering, Universitas Sultan Ageng Tirtayasa, 2025)
Oyster mushrooms often struggle to grow optimally due to unpredictable environmental factors like temperature, air humidity, and growing medium moisture. To address this, an IoT-based automation system with Mamdani fuzzy logic and MQTT communication was developed to carefully regulate these conditions. This study created such a system to optimize the growing environment. It uses a DHT22 sensor to monitor temperature and humidity, a capacitive soil moisture sensor connected to an ESP32 microcontroller, and a Mitsubishi FX3U-14MR PLC for management. Mamdani fuzzy logic and the MQTT protocol process and share data in real-time. Tests show the system is highly accurate, with an error rate below 5% compared to manual calculations, while also reducing crop failure risks, speeding up harvests by up to one day compared to traditional methods, and enhancing yield quality and efficiency. This approach offers a practical, scalable solution for modern oyster mushroom farming, minimizing human effort and ensuring environmental stability.